Analysis of response of vitiligo to treatment with NBUVB - Madhava Praveen, J.; Sidhwa, Jatin (International Journal of Research in Dermatology, 2019)
Background: Vitiligo is an acquired skin disorder characterised by white (depigmented) patches in the skin, due to the loss of functioning melanocytes. The disease can have devastating consequences on an individual’s relationships with others and internal feelings of self-worth. Vitiligo is caused by a dynamic interplay between genetic and environmental risks that initiates an autoimmune attack on melanocytes in the skin. Long term phototherapy has shown good response in the management of vitiligo. In this study we explore the efficacy of phototherapy in management of our vitiligo patients. Methods: 30 subjects were included in the study. Subjects were started on NBUVB at 300mj/cm2. Weekly 3 doses were given. Doses were increased after every 3rd sitting by 10%. In case of adverse effects treatment is withheld till resolution of symptoms following which NBUVB is given at 50% of the last dose and patient managed based on the response. Results: A majority of the subjects showed significant and persistent improvement within the first 3 months of initiation of treatment. The proportion of the patients showing improvement increased with duration of treatment. Conclusions: Our study has revealed the standard and significant role the phototherapy plays in the treatment of vitiligo as a monotherapy or as an adjuvant with other treatment modalities. With good treatment response and minimal side effect incidence, phototherapy is an important treatment modality in the management of vitiligo.